Strategi Meningkatkan Kepercayaan Konsumen Dalam Bisnis Online Home Bouquet Di Depok - Husnanei, Ade; Mufida, Hyifa; Kurniawati, Hartin (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
Business is an activity carried out by humans as one of the activities that can be profitable and provide added value through the interaction process of service delivery, production of goods, and distribution of goods or markets. To develop an online business, it is necessary to prioritize and find solutions to existing problems.one of the problems that exist in this business is consumer trust. In this case, strategies to increase consumer trust are such as ability, benevolence and integrity. These three strategies are implemented so that they can attract consumer confidence by more than 70% from before. And get a profit of Rp. 2,535,000 or 2x the previous profit.